Boom and bust methodology: Opportunities and challenges with conducting research at sites of resource extraction. Issue 4 (December 2015) - Jenkins, Jeffrey; Boone, Karie; Bosworth, Kai; Lehman, Jessi; Loder, Thomas
Highlights: Fieldwork in communities impacted by extractive development is associated with methodological challenges such as subjectivity and positionality. These challenges are greatly amplified by the rapid physical and political change in boom and bust economic activity. This rapidly changing nature at sites of resource extraction also allows opportunities for researchers to engage with stakeholders networks and become part of those networks in novel ways. This article is divided into the following themes: institutional permanence and extractive impermanence, subterranean knowledge, daily life and distemporal processes of extraction, positionality and family ties. Abstract: Researchers conducting fieldwork at sites of resource extraction experience unique challenges associated with methodology, such as subjectivity and positionality. These challenges are further amplified through the boom and bust nature of extraction. However, these rapidly changing physical and political landscapes also give way to unique opportunities to engage with communities undergoing socioeconomic change. Commentary from researchers working in communities impacted by the development of hydraulic fracturing activity and associated infrastructure highlights the tensions and perspectives that emerge from institutional permanency, knowledge of the subterranean, oral histories, and family ties. Although these cases focus on fieldwork conducted in the American west, it is our hope that this commentary may further the discussion of issues related to boom and bust methodology to sites of resource extraction beyond North America.